(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Background: COVID-19 has created a worldwide health emergency status and super spreading in the community of Bangladeshi population causing morbidity and mortality. Objectives: To find out the knowledge and attitude of medical students towards the Covid-19 pandemic during the lockdown situation. Methodology: This online cross sectional study was conducted from 1st to 31st May 2020 during the lockdown period in Bangladesh. Sample collection proforma was uploaded on the Google forms and links were shared on different social platforms. Data was analyzed by SPSS IBM version 22.00. Results: A total of 269 responses were obtained. The majority of the participants 167 (62.1%) were female and 102 (44.6%) belonged to an age group of 20-24 years. Most of the 91(33.8%) participants were 4th years students followed by 87(32.3%) from 3rd year. Majority of participants 230(85.5%) believe COVID-19 affect all age group, 187(69.5%) thinks that it affect the elder people seriously, 115(42.8%) thinks specific treatment may be available for COVID-19, 184(68.4%) says COVID-19 infection is preventable, 242(90%) opted for government lockdown and 225(83.6%) believed physical distancing is needed to prevent spread of this disease. Most of the participants 232(86.3%) complained about absence of diagnostic facilities in their neighboring area, 231(85.9%) thought common sign symptoms included dry cough, fever, fatigue and difficulty in breathing, most 234(87%) of the respondents thinks early supportive and symptomatic treatment can be helpful in cure of COVID-19 infection, 230(85.5%) gave positive opinion about isolation from the people who are infected with the COVID-19 virus is an effective way to reduce the spread of the virus . Regarding 14 days quarantine period 222(82.5%) give positive answer, 169(62.8%) thought COVID-19 would affect world economy badly, 172(63.9%0 thought common people are facing problem to collect daily needs, 184(68.4%) gave positive response that COVID-19 pandemic affects mental health of population, 93(34.6%) thought the situation may be controlled soon, majority 97(36.1%) answered they may be satisfied by current practices and initiatives taken by the government, almost all participants 265(97.4%) appreciated the efforts of healthcare providers for their society, 262(97.4%) of the participants thought there is need of more general awareness about COVID-19 pandemic and 260(96.7%) recommended procedure for repeated washing hands. Conclusion: An increasing awareness is needed amongst the local population regarding COVID-19 is required. It will lend hands in preventing spread of COVID-19 with minimal secondary transmission. More elaborate survey studies are required in future that can provide supportive data in developing and implementing public health policies regarding COVID-19 pandemic in our country. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 22-26